Spatial learning depends on both the addition and removal of new hippocampal neurons - Dupret, D; Fabre, A; Döbrössy, MD; Panatier, A; Rodríguez, J; Lamarque, S; Lemaire, V; Oliet, S; Piazza, P; Abrous, D (Public Library of Science, 2007)
The role of adult hippocampal neurogenesis in spatial learning remains a matter of debate. Here, we show that spatial learning modifies neurogenesis by inducing a cascade of events that resembles the selective stabilization process characterizing development. Learning promotes survival of relatively mature neurons, apoptosis of more immature cells, and finally, proliferation of neural precursors. These are three interrelated events mediating learning. Thus, blocking apoptosis impairs memory and inhibits learning-induced cell survival and cell proliferation. In conclusion, during learning, similar to the selective stabilization process, neuronal networks are sculpted by a tightly regulated selection and suppression of different populations of newly born neurons.